DAVSS: Development of Mobile Application for Documenting and Assessing Domestic Violence - Faiqah Hafidzah Halim; Nor Aimuni Md Rashid; Noor Azhana Abdul Majid (Journal of Artificial Intelligence and Technology, 2024)
This paper presents the development and evaluation of the Domestic Abuse and Violence Support System (DAVSS), a mobile application designed to address domestic violence issues in Malaysia. DAVSS integrates the essential 27-DASH (Danger Assessment for Separation and Harassment) questionnaire to assess the severity of domestic violence situations. The project follows the phased approach of the Waterfall Model, encompassing requirements, analysis, design, development, and testing stages.Usability testing was conducted to evaluate the DAVSS application, revealing overall user satisfaction. However, this assessment relied primarily on frequency analysis, prompting consideration for enhanced reliability through alternative measurement methods such as median and standard deviation approaches.The DAVSS application's Danger Assessment Test (DAT) algorithm, built upon the 27-DASH questions, represents a significant aspect of the system. Future work includes the validation of this rule-based algorithm using expert evaluation, potentially through Delphi techniques.Given the absence of dedicated domestic abuse mobile applications in Malaysia, DAVSS promises several advantages. It empowers victims to report incidents, locate shelters for protection, and facilitates shelter access through QR code integration. In conclusion, as domestic violence remains a pressing concern requiring increased support, the DAVSS mobile application emerges as a vital system that offers assistance to victims while breaking down barriers that may silence their voices.